A nova CEPAL e o mal-estar social na América Latina: uma alternativa de desenvolvimento? - Corrêa, Hugo Figueira de Souza (2007)
The main objective of this essay is to analyze critically the ECLAC s scientific production in the post-1980 decades, the so called New ECLAC. The hypothesis here undertaken is: after the changes suffered by ECLAC, that institution can no longer be placed side by side with the ones who seeks for real alternatives to the Neoliberalism the hegemonic development strategy of nowadays. Looking specifically to the welfare economics and social policies issues, it is argued that Neoliberalism and the ECLAC became closer perspectives and started to share the same world view. This dissertation seeks to clarify the debate over the real development alternatives for Latin American economies.